Development of a Novel Device for Harnessing Wasted Energy Behind a Marine Propeller. (2017) - Fuad, Nafis; Chowdhury, Mohammad Kifayath; Yasin, Mohammad Salman; Karim, Md. Mashud
Abstract: The energy dissipated due to the movement of fluid for the rotation of a propeller is somewhat wasted. A novel device is developed to harness this energy installing aturbine with zero pitch behind the ship propeller. Experiments are conducted with turbine having various radii and numbers of blades. The distance of the turbine from the ship propeller is varied and its effect is observed. For different arrangements, the energy harnessed by the turbine and the reduction in ship speed due to the presence of the device were measured. Data found in the experiment was used to find out a regression relationship among the parameters and a C++ program was developed to find out the optimum radius and number of blades of turbine and its distance from the propeller. The rotary motion of turbine can be used for driving generator to produce electricity to be consumed by the ship itself.